KEMAMPUAN BAYAM CABUT (Amaranthus tricolor L.) DALAM MENTRANSLOKASIKAN LOGAM TIMBAL PADA BERBAGAI DOSIS DAN WAKTU PEMBERIAN EDTA - ika aprilia rahayu putri (AGRONISMA, 2020)
The ability of spinach extract (is needed to help the effectiveness of the phytoremediation process undertaken. The use of EDTA as a chelating agent that can increase the mobility of metals in the soil leading to plants. The purpose of this study was to determine the interaction of EDTA doses and the timing of administration of the ability of spinach to pull (Amaranthus tricolor L.) in translating Pb metal. Field experiments using a Randomized Block Design (RCBD) arranged factorial with a control with three replications. The first factor EDTA dose, EDTA dose P1 = 3 gr and P2 = 6 gr. The second factor when giving EDTA, W1 = 7 dbt, W2 = 7 dat and W3 = 14 dat. The results showed that there was a real interaction between EDTA dose and time of EDTA administration. the treatment of P1W2 (EDTA dose 3 gr + 7 dat ) results in good growth changes in the parameters of observation of plant height, number of leaves, leaf area, total root length, total chlorophyll, and total concentration of lead metal absorbed as much 619.48 ppm